A Study of Coastal Communities’ Perception on Post Implementation Coremap in Sikka Regency - Barnabas Pablo Puente Wini Bhokaleba; Luky Adrianto; Maria Imaculata Rume (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
The implementation of Coremap programme in Sikka Regency in 2001 to 2011 was aimed to minimize the corals degradation and deterioration as the effect of irresponsible utilization and coastal management. This study was aimed to analyze coastal community perception about the implementation of Coremap I and II programme. The method that used in this study was survey method. The data in this study was obtained through direct interview and questioners. The respondents of this study were reef fish fishermen and the group of stakeholder namely religious leaders, community leaders and tribal figures, the users and Coremap management programme. There were several points that have been revealed such as a) the coastal community had already known about the existence of Coremap programme, b) most of the respondent had participated in Coremap programme, c) the Coremap programme was not really significant to increase the reef fish fishermen communities income in Sikka regency, d) there were still destructive fishing activities which done by local fishermen and fishermen from other places.